Light Detection For White Asparagus Farm Using Arduino - Bintang Ramadhan Prasetya; Galih Suryo Gumilang; Yogi Saputra; Joni Welman Simatupang (President University, 2020)
Nowadays, Technology has been a part of human life. in the world of agriculture, the existence of technology greatly helps plant productivity. Automation in the world of agriculture becomes the new norm, in many aspects of the field, such as in optimizing plant growth. One particular plant which requires delicate environment condition is white asparagus which could only grow optimally under low to no light environment. This project is a device to detect light in the plant room. When the light intensity passes certain threshold, an alarm is activated and a warning message is sent through Short Messaging Service to the owner’s cellphone. In addition, this device is also equipped by fire sensor to detect fire in the planting area and provides warning through the same channel. The test of the device gave promising results to be developed further in real planting area.